"Unique Hybrid Work model- The future of remote work" - Dr. Reena (Mahapatra) Lenka (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
COVID-19 pandemic has drastically changed the usual working norms of organizations worldwide. The entire world is trying to cope up in every possible way to overcome the unprecedented situation. The organizations worldwide are trying to adopt many new norms which were never dreamt of before. The entire world had never dreamt that remote work would be the new work norm. It is really hard to believe that one day such a situation would arise where everyone would be forced to work from home. Remote work has its share of challenges. Most of the organizations are still trying to cope up with this new norm. Challenges in the form of employee engagement, motivation, decrease communication, employee mental health and wellbeing, performance management, job security, stress and job satisfaction are wreaking havoc in the job market. organizations performance is greatly affected. Organizations worldwide are embracing a new concept in the form of Hybrid work model which will help in curbing the remote work challenges. This paper will help the readers to understand the concept of hybrid work model and also explain the benefits of this model. This paper will also give a glimpse regarding a unique Hybrid model if followed will help the organizations to overcome many challenges faced by Human resource managers due to remote work.